The effects of diversity management and inclusion on organisational outcomes: A case of multinational corporation - Folakemi Ohunakin; Anthonia Adenike Adeniji; Olaleke Oluseye Ogunnaike; Friday Igbadume; Dayo Idowu Akintayo (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
This article provides an empirical study on effects of diversity management and inclusion on organisational outcomes. The importance of diversity management and inclusion on organisation is of immense benefit especially in a Multinational Corporations, where diversity and inclusion are parts of their core values. However, in our context, which had been identified as the most diverse country in Africa, there is need to establish how the management and inclusion of these diverse workforce would benefit organisational activities, coupled with the fact that, there is dearth of research on these constructs in extant literature. This study investigated the effects of diversity management and inclusion on organisational outcomes (job satisfaction and job performance) among Shell Corporation employees. Pen and paper questionnaire of 384 copies were administered to the Lagos Branch employees of Shell Corporation. Cross-sectional research design was adopted. Confirmatory Factor Analysis (CFA), convergent and divergent validity, correlational analysis, and structural equation model were used for the analysis. The findings showed positive effect of diversity management and inclusion on employees' job satisfaction and employees' job performance. It implies that diversity management and inclusion have the potentials of assisting organisation in creating a climate in which employee will like to work harder with readiness to continue to work with the organisation.
Keywords: M54; 650; diversity management; inclusion; job satisfaction; job performance; Shell Corporation; Nigeria